Shipping the Good Apples Out Under Asymmetric Information - Anthony Creane; Thomas D. Jeitschko (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2012)
The importance of institutions for economic growth has gathered considerable interest. For example, weak institutions can prevent firms from communicating their quality, which can lead to lower welfare. We explore how and whether exporting to markets with strong institutions may alleviate this when firms have high and low quality goods. Surprisingly, we find that access to developed markets can exacerbate the problems caused by weak institutions and harm home welfare. First, exporting can harm home welfare: the country is better off if all exporting were prevented. Second, any harm is increasing in the amount exported. Third, if not all high quality is exported, then home welfare can always be increased by restricting exports. Fourth, the opening of trade can reduce producer surplus and so in the long run lead to a reduction in the production of the export good. Fifth, welfare can decrease even if production of the exported good increases.
Keywords: 330